Demand-sensitive schooling? : Evidence and issues - Istance, David; Centre for Educational Research and Innovation; Organisation for Economic Co-operation and Development (Paris : b OECD, 2006)
Many educational experts are identifying a critical shift from from supply-led systems, operating to procedures decided by educational authorities, schools and teachers, towards systems which are much more sensitive to demand. But whose demands should these be? What are they? And how will schools recognize and cope with them? This book examines different aspects of the demand concept and presents international evidence from Austria, the Czech and Slovak Republics, Denmark, England, Finland, Hungary, Japan, Poland, Spain, and the United States to reveal attitudes and expectations.--Publisher's description
Exploring the concept of demand -- Public and parental perceptions of schooling -- Parental choice and diversity of provision -- Parent and community'voice' in schools -- What do the students say? -- The demand dimensions : concluding issues and directions
'Centre for Educational Research and Innovation.'
'Project leader David Istance was responsible for this report, along with Henno Theisens. Delphine Grandrieux and Jennifer Cannon prepared and edited the text'--p. 4.
Includes bibliographical references
Keywords: Education -- OECD countries; Education and state -- OECD countries